2022
DOI: 10.1007/s10570-022-04499-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue paper-based composite separator using nano-SiO2 hybrid crosslinked polymer electrolyte as coating layer for lithium ion battery with superior security and cycle stability

Abstract: With the development of energy-storage devices, separator is encountered by several challenges including adequate safety, higher current density and superior stability. Tissue paper, composed of packed cellulose bers, possesses lower production cost, more easily accessibility, superior wettability and outstanding thermostability, thus being prospective as a substrate of high performance separator. To address structure collapse phenomenon occurred in conventional coating layer after long term electrolyte swelli… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…The Li + transfer number of Li/CME/Li batteries was 0.5 and 0.49, respectively, and was higher than the Celgard separator (0.26) and CM25 separator (0.2), which demonstrated that the mobility of solvated anions was restricted in the solvent channels of CME separators. This is due to two reasons: (1) the PF 6 ions were physically suppressed by the three-dimensional network of CME separators [55]; (2) the electrolyte anions (PF 6 ) as a Lewis acid were trapped by the Lewis base (-NH2), allowing more Li + to migrate during the charge/discharge process [56]. This further verifies the influence of -NH2 on anion transport in the chitosan fiber separators.…”
Section: Electrochemical Performancesmentioning
confidence: 57%
“…The Li + transfer number of Li/CME/Li batteries was 0.5 and 0.49, respectively, and was higher than the Celgard separator (0.26) and CM25 separator (0.2), which demonstrated that the mobility of solvated anions was restricted in the solvent channels of CME separators. This is due to two reasons: (1) the PF 6 ions were physically suppressed by the three-dimensional network of CME separators [55]; (2) the electrolyte anions (PF 6 ) as a Lewis acid were trapped by the Lewis base (-NH2), allowing more Li + to migrate during the charge/discharge process [56]. This further verifies the influence of -NH2 on anion transport in the chitosan fiber separators.…”
Section: Electrochemical Performancesmentioning
confidence: 57%
“…Interfacial compatibility between separator and lithium electrode is another factor to decide ohmic polarization in LIB, [43] which can be judged from interfacial impedance plots of Li/separator/Li cell as shown in Figure 7(b). We could find two semicircles located at medium and low frequency regions, which were respectively attributed to solid electrolyte interface film impedance ( R SEI ) and charge transfer impedance ( R ct ) [44] .…”
Section: Resultsmentioning
confidence: 99%
“…The effective strategy to improve the electrochemical performance with stable mechanical stability is the addition of inert metal oxide fillers to the polymer matrix. Especially the incorporation of inorganic oxide fillers, such as TiO 2 , SiO 2 , ZrO 2 , Al 2 O 3 , and BN etc ., has an impactful increase in amorphous nature with the addition of an appropriate amount in polymer electrolyte. The inert inorganic oxide fillers dispersed in polymer solution are a better influencing agent in retaining the amorphous nature, which transfers the lithium ions under segmental motion in polymer electrolyte. , Nevertheless, preparing these inorganic fillers requires huge costs with profound preparation techniques such as solid-state, sol–gel, sputtering, chemical vapor deposition, etc.…”
Section: Introductionmentioning
confidence: 99%